Antibacterial titanium-silver alloy material and preparation method thereof

CN122879622APending Publication Date: 2026-10-09江苏昊冠精密机械制造有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610951540.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

现有抗菌钛银合金多采用熔铸法制备,易导致Ag元素宏观偏聚,抗菌性能不均且稳定性差;氧间隙原子易引发材料脆化,大幅降低力学可靠性

Benefits of technology

与现有技术相比,本发明所达到的有益效果是:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to a kind of antibacterial titanium silver alloy material and its preparation method, belong to titanium silver alloy material technical field.The present application first with TiO2, Ag2O, B2O3, La2O3, CeO2 as precursor powder, using CaCl2-NaCl binary eutectic molten salt as main body, added CaF2 as functional deoxidizing agent as reaction medium, by multivariate molten salt pulse co-reduction, SPS two-step sintering, double-stage pulse, composite micro-arc oxidation is prepared antibacterial titanium silver alloy material.Gradient potential pre-reduction, ultrasonic dispersion, Ar-H2 deep deoxidation realize element homogenization and toughening, synergistic TiB whisker physical film breaking and Ag + Chemical sterilization forms double-effect antibacterial system, while in-situ generates dense film containing La2O3 / CeO2 to improve corrosion resistance.The titanium silver alloy prepared by the present application has excellent mechanical, antibacterial and corrosion-resistant effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium-silver alloy materials technology, specifically to an antibacterial titanium-silver alloy material and its preparation method. Background Technology

[0002] Titanium and titanium alloys are widely used in medical implants and marine engineering due to their high specific strength and good biocompatibility. However, pure titanium lacks antibacterial properties, easily leading to postoperative bacterial infection and corrosion failure. Existing antibacterial titanium-silver alloys are mostly prepared using a casting method, which easily leads to macroscopic segregation of Ag elements, resulting in uneven antibacterial performance and poor stability; interstitial oxygen atoms can easily cause material embrittlement, significantly reducing mechanical reliability. Chemical sterilization mechanisms have limited antibacterial efficiency, and titanium alloys themselves lack sufficient corrosion resistance, making them vulnerable to erosion under complex service environments. Furthermore, existing molten salt reduction processes suffer from insufficient deoxidation, rare earth element segregation, grain growth during sintering, uncontrollable antibacterial phase precipitation, poor density and limited functionality of the micro-arc oxide film, failing to simultaneously achieve synergistic optimization of mechanical, antibacterial, and corrosion-resistant properties. This hinders the large-scale application and service life extension of antibacterial titanium-silver alloys. Summary of the Invention

[0003] The purpose of this invention is to provide an antibacterial titanium-silver alloy material and its preparation method, so as to solve the problems existing in the prior art.

[0004] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing an antibacterial titanium-silver alloy material, comprising the following steps: (1) Titanium dioxide, silver oxide, boron oxide, lanthanum oxide, cerium oxide and yttrium oxide are mixed in a mass ratio of 8.5~9.5:2~4:0.1~0.3:0.1~0.3:0.1~0.3:0.05~0.15, wet-milled for 3~5 hours, vacuum dried at 80℃ for 12 hours and sieved to obtain precursor powder, cold-pressed into blocks, and pre-sintered as electrolytic cathode; anhydrous calcium chloride: anhydrous calcium fluoride: anhydrous sodium chloride are mixed in a mass ratio of 8.5~9.5:4~6:2~4, heated to 850℃ under a high-purity argon atmosphere, the pre-sintered cathode block is immersed in molten salt, and a high-purity graphite rod is used as the anode to perform gradient multi-element molten salt pulse co-reduction to obtain pre-alloy powder; (2) After the pre-alloyed powder is sintered by SPS in two steps, it is kept at 950℃, then quenched and cooled, and then subjected to a two-stage pulse aging treatment: the first stage of aging is the pre-precipitation of silver nano-islands, and the quenched block is kept at 400℃ for 6 hours; the second stage of pulse aging is to attach copper electrodes to both ends of the block after the first stage of aging and connect them to a pulse power supply. A pulse current is applied under argon protection, and the block is naturally cooled in the argon flow to obtain the block; (3) The aged block is connected with aluminum wire as the anode and stainless steel electrolytic cell as the cathode. Electrolyte is added and composite micro-arc oxidation treatment is carried out. After the treatment is completed, it is placed in deionized water and hydrothermally treated at 80°C for 2 hours. Then it is vacuum dried at 60°C for 12 hours to obtain antibacterial titanium silver alloy material.

[0005] Furthermore, the titanium dioxide in step (1) is titanium dioxide with a particle size of 100 nm.

[0006] Furthermore, the sieving in step (1) is: sieving through a 200-mesh sieve.

[0007] Further, the cold pressing molding block in step (1) is as follows: the mixed precursor powder is cold pressed at 10MPa on a uniaxial press to form a cylindrical block with a diameter of 20mm and a thickness of 5mm.

[0008] Furthermore, the heating rate in step (1) is 5℃ / min.

[0009] Furthermore, the high-purity graphite rod mentioned in step (1) is a high-purity graphite rod with a diameter of 10 mm.

[0010] Furthermore, the pre-alloyed powder in step (1) is: pre-alloyed powder that has passed through a 300-mesh sieve.

[0011] Furthermore, the block after aging treatment in step (2) is a dense alloy block with a diameter of 20 mm and a height of 10 mm.

[0012] Furthermore, the electrolyte in step (3) is prepared by mixing sodium silicate nonahydrate, potassium hydroxide, lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, silver nitrate and deionized water in a mass ratio of 15:3:1:1:0.3:1000 and stirring at room temperature for 15 minutes.

[0013] Furthermore, the composite micro-arc oxidation treatment in step (3) is as follows: the first stage is constant current film formation: at a current density of 10 A / dm 2 Under the conditions of a pulse frequency of 800Hz and a duty cycle of 20%, the voltage is gradually increased from 0 to 400V to generate a porous titanium dioxide base film. The second stage is constant-voltage densification and elemental doping: the voltage is stabilized at 400V and maintained for 3 minutes, then increased to 450V in a gradient of 5V every 10 seconds, followed by constant-voltage treatment until the current density decays to 1A / dm³. 2 termination Compared with the prior art, the beneficial effects achieved by the present invention are: This invention involves a multi-step synergistic treatment of precursor powder to achieve excellent mechanical, antibacterial, and corrosion-resistant properties.

[0014] This invention first uses TiO2, Ag2O, B2O3, La2O3, and CeO2 as precursor powders, and employs CaCl2-NaCl binary eutectic molten salt as the main component, with CaF2 added as a functional deoxidizing agent as the reaction medium. An antibacterial titanium-silver alloy material is prepared through multi-component molten salt pulsed co-reduction, SPS two-step sintering, dual-stage pulse, and composite micro-arc oxidation. Salt reduction utilizes a gradient potential pulsed electrolysis mechanism to pre-reduce TiO2 to porous TiH2, leveraging its nanopores to adsorb and disperse La. 3+ Ce 3+ B 3+ Ions are then synchronously pulsed to reduce all oxides, and ultrasonication is used to break the rare earth concentration boundary layer to inhibit segregation. Later, an Ar-H2 mixed gas is introduced for deep deoxidation, eliminating the embrittlement of interstitial oxygen atoms and achieving uniform dispersion of all elements, thus endowing the material with excellent mechanical and antibacterial properties. The SPS two-step sintering process, combined with grain boundary inhibitors, forms TiB whiskers. Furthermore, dual-stage pulsed aging induces the pre-precipitation of Ag nano-islands and the directional growth of TiB whiskers at the Ag tips, resulting in physical film breaking of the whiskers and Ag... + The dual-effect antibacterial system, combining chemical sterilization and chemical disinfection, significantly enhances the antibacterial properties of the material. Micro-arc oxidation, through rare-earth composite electrolyte and gradient voltage film formation, generates a dense film containing La2O3 / CeO2 in situ. This dense film acts as a physical barrier, directly blocking corrosive media and greatly improving the material's corrosion resistance. Simultaneously, it can slowly release La... 3+ / Ce 3+ It disrupts the integrity of bacterial cell membranes, thereby further enhancing antibacterial properties. Detailed Implementation

[0015] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0016] To more clearly illustrate the method provided by the present invention, the following embodiments are provided in detail. The testing methods for various properties of the titanium-silver alloy material prepared in the following embodiments are as follows: Antibacterial performance testing: The alloy materials prepared in Examples 1-5 and Comparative Examples 1-6 were tested according to the determination method published in the national standard GB / T 24170.1-2009 "Surface Antibacterial Stainless Steel Part 1: Electrochemical Method", using Escherichia coli and Staphylococcus aureus as test bacteria. Compressive strength test: The alloy materials prepared in Examples 1-5 and Comparative Examples 1-6 were tested according to GB / T 7314-2017 "Metallic Materials - Room Temperature Compression Test Method".

[0017] Corrosion resistance test: Salt spray corrosion tests were conducted on the alloy materials prepared in Examples 1-5 and Comparative Examples 1-6 in accordance with the "Standard Operating Procedure for Salt Spray Test after Modification of ASTM G85-2011 and its Appendix A3 Seawater Acidification Cyclic Test". Example 1

[0018] (1) Titanium dioxide, silver oxide, boron oxide, lanthanum oxide, cerium oxide and yttrium oxide with a particle size of 100 nm were mixed in a mass ratio of 8.5:2:0.1:0.1:0.1:0.05. Anhydrous ethanol was used as the medium and the mixture was wet-milled at 300 rpm for 3 h with a ball-to-material ratio of 5:1. The slurry was vacuum-dried at 80 °C for 12 h and then ground through a 200-mesh sieve to obtain a uniformly mixed precursor powder. (2) The mixed precursor powder was cold-pressed at 10 MPa on a uniaxial press to form a cylindrical block with a diameter of 20 mm and a thickness of 5 mm. The block was placed in a tube furnace and heated to 950 °C at 5 °C / min under argon protection, and held for 3 h for pre-sintering. After cooling in the furnace, the block was removed. The pre-sintered block was bound and fixed with molybdenum wire as an electrolytic cathode. Anhydrous calcium chloride, anhydrous calcium fluoride and anhydrous sodium chloride were mixed at a mass ratio of 8.5:4:2. Under a high-purity argon atmosphere, the mixture was heated to 850 °C at 5 °C / min. After the molten salt was completely melted and stabilized, the pre-sintered cathode block was immersed in the molten salt. A high-purity graphite rod with a diameter of 10 mm was used as the anode for multi-element molten salt pulse co-reduction. (3) The first stage lasts for a total of 3 hours. First, the cathode potential is set to -1.8V and the pulse duty cycle is 1:2, that is, energizing for 10 milliseconds and de-energizing for 20 milliseconds. Titanium dioxide is partially reduced to porous titanium hydride. The generated nanopores are used to physically adsorb lanthanum ions, cerium ions and borate ions in the molten salt to achieve atomic-level uniform dispersion and suppress rare earth element segregation from the source. Second, the second stage lasts for a total of 8 hours. First, the cathode potential is set to -2.2V and the pulse duty cycle is 1:1, that is, energizing for 15 milliseconds and de-energizing for 15 milliseconds. At the same time, an ultrasonic field is applied to the molten salt area at 20kHz, with a 2-minute pause every 5 minutes of operation, to break the rare earth element segregation. The concentration boundary layer of earth ions on the cathode surface ensures the simultaneous reduction of the five elements and the formation of a homogeneous solid solution. During the last hour of this process, the protective atmosphere is switched to a mixture of 95% argon and 5% hydrogen (by volume), which is introduced into the space above the molten salt at a flow rate of 200 mL / min. The hydrogen participates in chemical reduction, further removing the oxygen content of the powder to an extremely low level. After electrolysis, the cathode block is lifted from the molten salt surface under argon protection and allowed to cool naturally to room temperature. The cathode block is then removed and repeatedly soaked in deionized water with mechanical stirring, changing the deionized water every 2 hours for 12 hours to fully dissolve and remove the adhering chloride molten salt. It is then soaked in 5% dilute acetic acid for 1 hour to neutralize any possible calcium oxides. Finally, it is rinsed three times with anhydrous ethanol and dried in a vacuum drying oven at 60°C for 24 hours. The dried, loose block is then ground and passed through a 300-mesh sieve to obtain pre-alloyed powder, which is then sealed and stored for later use. (4) The pre-alloyed powder is subjected to two-step SPS sintering. The first step is the pre-densification stage: the temperature is increased to 750℃ at a rate of 100℃ / min and held for 5min. During this period, the pressure is increased to 40MPa. In this stage, surface diffusion and local plastic deformation occur between powder particles, achieving preliminary densification while retaining the nanostructure inside the powder. The second step is the full densification stage: the temperature is increased to 900℃ at a rate of 80℃ / min and held for 3min. During this period, the pressure is increased to 50MPa and maintained. In this stage, the bulk is fully densified. Under the combined action of high temperature and electric field, boron reacts with titanium to generate titanium boride whiskers in situ. Yttrium oxide plays the role of grain boundary inhibitor in this stage, pinning grain boundary migration. After sintering, it is rapidly cooled with the furnace to obtain a dense alloy bulk with a diameter of 20mm and a height of 10mm. (5) The SPS sintered block was held at 950℃ for 45 min, and then quickly immersed in an ice-salt mixture for quenching and cooling. The silver phase precipitated during the sintering stage was re-dissolved into the matrix to form a supersaturated solid solution. Then, a two-stage pulse aging treatment was performed: the first-stage aging stage was for the pre-precipitation of silver nano-islands. The quenched block was placed in a vacuum tube furnace and held at 400℃ for 6 h. During this stage, silver atoms were uniformly precipitated from the supersaturated solid solution to form diffusely distributed silver nano-islands with a size of 10 nm. At the same time, boron atoms began to agglomerate, which provided a driving force for the further growth of titanium boride. The second-stage pulse aging stage was for the directional growth and microstructure coupling of titanium boride. Copper electrodes were attached to both ends of the block after the first-stage aging and connected to a pulse power supply. A pulse current was applied under argon protection with a peak current density of 80 A / mm. 2 The pulse width was 2 ms, the frequency was 80 Hz, the on-time to off-time ratio was 1:3, and the total processing time was 30 min. Driven by both thermal and non-thermal effects of the pulsed current, titanium boride underwent directional growth using precipitated silver nanoislands as heterogeneous nucleation sites, ultimately forming a physical film of silver enriched at the tips of titanium boride whiskers and Ag. + A dual-effect antibacterial system combining chemical sterilization and disinfection. Power is cut off after treatment, and the system cools naturally in an argon gas flow. (6) Sodium silicate nonahydrate, potassium hydroxide, lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, silver nitrate, and deionized water were mixed in a mass ratio of 15:3:1:1:0.3:1000 and stirred at 300 rpm for 15 min at room temperature to obtain an electrolyte. The aged block was connected with an aluminum wire as the anode, and a stainless steel electrolytic cell was used as the cathode. The electrolyte was added to perform composite micro-arc oxidation treatment. The first stage was constant current film formation: at a current density of 10 A / dm 2 Under the conditions of a pulse frequency of 800Hz and a duty cycle of 20%, the voltage is gradually increased from 0 to 400V to generate a porous titanium dioxide base film. The second stage is constant-voltage densification and elemental doping: the voltage is stabilized at 400V and maintained for 3 minutes, then increased to 450V in a gradient of 5V every 10 seconds, followed by constant-voltage treatment until the current density decays to 1A / dm³. 2 After the treatment was terminated, the material was placed in deionized water and hydrothermally treated at 80°C for 2 hours to seal any remaining micropores in the membrane. Subsequently, it was vacuum dried at 60°C for 12 hours to obtain the antibacterial titanium-silver alloy material.

[0019] Example 2 (1) Titanium dioxide, silver oxide, boron oxide, lanthanum oxide, cerium oxide and yttrium oxide with a particle size of 100 nm were mixed in a mass ratio of 8.8:2.5:0.15:0.15:0.15:0.08. Anhydrous ethanol was used as the medium and the mixture was wet-milled at 300 rpm for 3.5 h with a ball-to-material ratio of 5:1. The slurry after milling was vacuum-dried at 80 °C for 12 h and then ground through a 200-mesh sieve to obtain a uniformly mixed precursor powder. (2) The mixed precursor powder was cold-pressed at 10 MPa on a uniaxial press to form a cylindrical block with a diameter of 20 mm and a thickness of 5 mm. The block was placed in a tube furnace and heated to 950 °C at 5 °C / min under argon protection, and held for 3 h for pre-sintering. After cooling in the furnace, the block was removed. The pre-sintered block was bound and fixed with molybdenum wire as an electrolytic cathode. Anhydrous calcium chloride, anhydrous calcium fluoride and anhydrous sodium chloride were mixed in a mass ratio of 8.8:4.5:2.5. Under a high-purity argon atmosphere, the mixture was heated to 850 °C at 5 °C / min. After the molten salt was completely melted and stabilized, the pre-sintered cathode block was immersed in the molten salt. A high-purity graphite rod with a diameter of 10 mm was used as the anode for multi-element molten salt pulse co-reduction. (3) The first stage lasts for a total of 3 hours. First, the cathode potential is set to -1.8V and the pulse duty cycle is 1:2, that is, energizing for 10 milliseconds and de-energizing for 20 milliseconds. Titanium dioxide is partially reduced to porous titanium hydride. The generated nanopores are used to physically adsorb lanthanum ions, cerium ions and borate ions in the molten salt to achieve atomic-level uniform dispersion and suppress rare earth element segregation from the source. Second, the second stage lasts for a total of 8 hours. First, the cathode potential is set to -2.2V and the pulse duty cycle is 1:1, that is, energizing for 15 milliseconds and de-energizing for 15 milliseconds. At the same time, an ultrasonic field is applied to the molten salt area at 20kHz, with a 2-minute pause every 5 minutes of operation, to break the rare earth element segregation. The concentration boundary layer of earth ions on the cathode surface ensures the simultaneous reduction of the five elements and the formation of a homogeneous solid solution. During the last hour of this process, the protective atmosphere is switched to a mixture of 95% argon and 5% hydrogen (by volume), which is introduced into the space above the molten salt at a flow rate of 200 mL / min. The hydrogen participates in chemical reduction, further removing the oxygen content of the powder to an extremely low level. After electrolysis, the cathode block is lifted from the molten salt surface under argon protection and allowed to cool naturally to room temperature. The cathode block is then removed and repeatedly soaked in deionized water with mechanical stirring, changing the deionized water every 2 hours for 12 hours to fully dissolve and remove the adhering chloride molten salt. It is then soaked in 5% dilute acetic acid for 1 hour to neutralize any possible calcium oxides. Finally, it is rinsed three times with anhydrous ethanol and dried in a vacuum drying oven at 60°C for 24 hours. The dried, loose block is then ground and passed through a 300-mesh sieve to obtain pre-alloyed powder, which is then sealed and stored for later use. (4) The pre-alloyed powder is subjected to two-step SPS sintering. The first step is the pre-densification stage: the temperature is increased to 750℃ at a rate of 100℃ / min and held for 5min. During this period, the pressure is increased to 40MPa. In this stage, surface diffusion and local plastic deformation occur between powder particles, achieving preliminary densification while retaining the nanostructure inside the powder. The second step is the full densification stage: the temperature is increased to 900℃ at a rate of 80℃ / min and held for 3min. During this period, the pressure is increased to 50MPa and maintained. In this stage, the bulk is fully densified. Under the combined action of high temperature and electric field, boron reacts with titanium to generate titanium boride whiskers in situ. Yttrium oxide plays the role of grain boundary inhibitor in this stage, pinning grain boundary migration. After sintering, it is rapidly cooled with the furnace to obtain a dense alloy bulk with a diameter of 20mm and a height of 10mm. (5) The SPS sintered block was held at 950℃ for 45 min, and then quickly immersed in an ice-salt mixture for quenching and cooling. The silver phase precipitated during the sintering stage was re-dissolved into the matrix to form a supersaturated solid solution. Then, a two-stage pulse aging treatment was performed: the first-stage aging stage was for the pre-precipitation of silver nano-islands. The quenched block was placed in a vacuum tube furnace and held at 400℃ for 6 h. During this stage, silver atoms were uniformly precipitated from the supersaturated solid solution to form diffusely distributed silver nano-islands with a size of 10 nm. At the same time, boron atoms began to agglomerate, which provided a driving force for the further growth of titanium boride. The second-stage pulse aging stage was for the directional growth and microstructure coupling of titanium boride. Copper electrodes were attached to both ends of the block after the first-stage aging and connected to a pulse power supply. A pulse current was applied under argon protection with a peak current density of 80 A / mm. 2 The pulse width was 2 ms, the frequency was 80 Hz, the on-time to off-time ratio was 1:3, and the total processing time was 30 min. Driven by both thermal and non-thermal effects of the pulsed current, titanium boride underwent directional growth using precipitated silver nanoislands as heterogeneous nucleation sites, ultimately forming a physical film of silver enriched at the tips of titanium boride whiskers and Ag. + A dual-effect antibacterial system combining chemical sterilization and disinfection. Power is cut off after treatment, and the system cools naturally in an argon gas flow. (6) Sodium silicate nonahydrate, potassium hydroxide, lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, silver nitrate, and deionized water were mixed in a mass ratio of 15:3:1:1:0.3:1000 and stirred at 300 rpm for 15 min at room temperature to obtain an electrolyte. The aged block was connected with an aluminum wire as the anode, and a stainless steel electrolytic cell was used as the cathode. The electrolyte was added to perform composite micro-arc oxidation treatment. The first stage was constant current film formation: at a current density of 10 A / dm 2Under the conditions of a pulse frequency of 800Hz and a duty cycle of 20%, the voltage is gradually increased from 0 to 400V to generate a porous titanium dioxide base film. The second stage is constant-voltage densification and elemental doping: the voltage is stabilized at 400V and maintained for 3 minutes, then increased to 450V in a gradient of 5V every 10 seconds, followed by constant-voltage treatment until the current density decays to 1A / dm³. 2 After the treatment was terminated, the material was placed in deionized water and hydrothermally treated at 80°C for 2 hours to seal any remaining micropores in the membrane. Subsequently, it was vacuum dried at 60°C for 12 hours to obtain the antibacterial titanium-silver alloy material. Example 3

[0020] (1) Titanium dioxide, silver oxide, boron oxide, lanthanum oxide, cerium oxide and yttrium oxide with a particle size of 100 nm were mixed in a mass ratio of 9:3:0.2:0.2:0.2:0.1. Anhydrous ethanol was used as the medium and the mixture was wet-milled at 300 rpm for 4 h with a ball-to-material ratio of 5:1. The slurry after milling was vacuum-dried at 80 °C for 12 h and then ground through a 200-mesh sieve to obtain a uniformly mixed precursor powder. (2) The mixed precursor powder was cold-pressed at 10 MPa on a uniaxial press to form a cylindrical block with a diameter of 20 mm and a thickness of 5 mm. The block was placed in a tube furnace and heated to 950 °C at 5 °C / min under argon protection, and held for 3 h for pre-sintering. After cooling in the furnace, the block was removed. The pre-sintered block was bound and fixed with molybdenum wire as an electrolytic cathode. Anhydrous calcium chloride, anhydrous calcium fluoride and anhydrous sodium chloride were mixed in a mass ratio of 9:5:3. Under a high-purity argon atmosphere, the mixture was heated to 850 °C at 5 °C / min. After the molten salt was completely melted and stabilized, the pre-sintered cathode block was immersed in the molten salt. A high-purity graphite rod with a diameter of 10 mm was used as the anode for multi-element molten salt pulse co-reduction. (3) The first stage lasts for a total of 3 hours. First, the cathode potential is set to -1.8V and the pulse duty cycle is 1:2, that is, energizing for 10 milliseconds and de-energizing for 20 milliseconds. Titanium dioxide is partially reduced to porous titanium hydride. The generated nanopores are used to physically adsorb lanthanum ions, cerium ions and borate ions in the molten salt to achieve atomic-level uniform dispersion and suppress rare earth element segregation from the source. Second, the second stage lasts for a total of 8 hours. First, the cathode potential is set to -2.2V and the pulse duty cycle is 1:1, that is, energizing for 15 milliseconds and de-energizing for 15 milliseconds. At the same time, an ultrasonic field is applied to the molten salt area at 20kHz, with a 2-minute pause every 5 minutes of operation, to break the rare earth element segregation. The concentration boundary layer of earth ions on the cathode surface ensures the simultaneous reduction of the five elements and the formation of a homogeneous solid solution. During the last hour of this process, the protective atmosphere is switched to a mixture of 95% argon and 5% hydrogen (by volume), which is introduced into the space above the molten salt at a flow rate of 200 mL / min. The hydrogen participates in chemical reduction, further removing the oxygen content of the powder to an extremely low level. After electrolysis, the cathode block is lifted from the molten salt surface under argon protection and allowed to cool naturally to room temperature. The cathode block is then removed and repeatedly soaked in deionized water with mechanical stirring, changing the deionized water every 2 hours for 12 hours to fully dissolve and remove the adhering chloride molten salt. It is then soaked in 5% dilute acetic acid for 1 hour to neutralize any possible calcium oxides. Finally, it is rinsed three times with anhydrous ethanol and dried in a vacuum drying oven at 60°C for 24 hours. The dried, loose block is then ground and passed through a 300-mesh sieve to obtain pre-alloyed powder, which is then sealed and stored for later use. (4) The pre-alloyed powder is subjected to two-step SPS sintering. The first step is the pre-densification stage: the temperature is increased to 750℃ at a rate of 100℃ / min and held for 5min. During this period, the pressure is increased to 40MPa. In this stage, surface diffusion and local plastic deformation occur between powder particles, achieving preliminary densification while retaining the nanostructure inside the powder. The second step is the full densification stage: the temperature is increased to 900℃ at a rate of 80℃ / min and held for 3min. During this period, the pressure is increased to 50MPa and maintained. In this stage, the bulk is fully densified. Under the combined action of high temperature and electric field, boron reacts with titanium to generate titanium boride whiskers in situ. Yttrium oxide plays the role of grain boundary inhibitor in this stage, pinning grain boundary migration. After sintering, it is rapidly cooled with the furnace to obtain a dense alloy bulk with a diameter of 20mm and a height of 10mm. (5) The SPS sintered block was held at 950℃ for 45 min, and then quickly immersed in an ice-salt mixture for quenching and cooling. The silver phase precipitated during the sintering stage was re-dissolved into the matrix to form a supersaturated solid solution. Then, a two-stage pulse aging treatment was performed: the first-stage aging stage was for the pre-precipitation of silver nano-islands. The quenched block was placed in a vacuum tube furnace and held at 400℃ for 6 h. During this stage, silver atoms were uniformly precipitated from the supersaturated solid solution to form diffusely distributed silver nano-islands with a size of 10 nm. At the same time, boron atoms began to agglomerate, which provided a driving force for the further growth of titanium boride. The second-stage pulse aging stage was for the directional growth and microstructure coupling of titanium boride. Copper electrodes were attached to both ends of the block after the first-stage aging and connected to a pulse power supply. A pulse current was applied under argon protection with a peak current density of 80 A / mm. 2 The pulse width was 2 ms, the frequency was 80 Hz, the on-time to off-time ratio was 1:3, and the total processing time was 30 min. Driven by both thermal and non-thermal effects of the pulsed current, titanium boride underwent directional growth using precipitated silver nanoislands as heterogeneous nucleation sites, ultimately forming a physical film of silver enriched at the tips of titanium boride whiskers and Ag. + A dual-effect antibacterial system combining chemical sterilization and disinfection. Power is cut off after treatment, and the system cools naturally in an argon gas flow. (6) Sodium silicate nonahydrate, potassium hydroxide, lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, silver nitrate, and deionized water were mixed in a mass ratio of 15:3:1:1:0.3:1000 and stirred at 300 rpm for 15 min at room temperature to obtain an electrolyte. The aged block was connected with an aluminum wire as the anode, and a stainless steel electrolytic cell was used as the cathode. The electrolyte was added to perform composite micro-arc oxidation treatment. The first stage was constant current film formation: at a current density of 10 A / dm 2 Under the conditions of a pulse frequency of 800Hz and a duty cycle of 20%, the voltage is gradually increased from 0 to 400V to generate a porous titanium dioxide base film. The second stage is constant-voltage densification and elemental doping: the voltage is stabilized at 400V and maintained for 3 minutes, then increased to 450V in a gradient of 5V every 10 seconds, followed by constant-voltage treatment until the current density decays to 1A / dm³. 2 After the treatment was terminated, the material was placed in deionized water and hydrothermally treated at 80°C for 2 hours to seal any remaining micropores in the membrane. Subsequently, it was vacuum dried at 60°C for 12 hours to obtain the antibacterial titanium-silver alloy material. Example 4

[0021] (1) Titanium dioxide, silver oxide, boron oxide, lanthanum oxide, cerium oxide and yttrium oxide with a particle size of 100 nm were mixed in a mass ratio of 9.3:3.5:0.25:0.25:0.25:0.13. Anhydrous ethanol was used as the medium and the mixture was wet-milled at 300 rpm for 4.5 h with a ball-to-material ratio of 5:1. The slurry after milling was vacuum-dried at 80 °C for 12 h and then ground through a 200-mesh sieve to obtain a uniformly mixed precursor powder. (2) The mixed precursor powder was cold-pressed at 10 MPa on a uniaxial press to form a cylindrical block with a diameter of 20 mm and a thickness of 5 mm. The block was placed in a tube furnace and heated to 950 °C at 5 °C / min under argon protection and held for 3 h for pre-sintering. After cooling in the furnace, the block was removed. The pre-sintered block was bound and fixed with molybdenum wire as an electrolytic cathode. Anhydrous calcium chloride, anhydrous calcium fluoride and anhydrous sodium chloride were mixed in a mass ratio of 9.3:5.5:3.5 and heated to 850 °C at 5 °C / min under a high-purity argon atmosphere. After the molten salt was completely melted and stabilized, the pre-sintered cathode block was immersed in the molten salt and a high-purity graphite rod with a diameter of 10 mm was used as the anode for multi-element molten salt pulse co-reduction. (3) The first stage lasts for a total of 3 hours. First, the cathode potential is set to -1.8V and the pulse duty cycle is 1:2, that is, energizing for 10 milliseconds and de-energizing for 20 milliseconds. Titanium dioxide is partially reduced to porous titanium hydride. The generated nanopores are used to physically adsorb lanthanum ions, cerium ions and borate ions in the molten salt to achieve atomic-level uniform dispersion and suppress rare earth element segregation from the source. Second, the second stage lasts for a total of 8 hours. First, the cathode potential is set to -2.2V and the pulse duty cycle is 1:1, that is, energizing for 15 milliseconds and de-energizing for 15 milliseconds. At the same time, an ultrasonic field is applied to the molten salt area at 20kHz, with a 2-minute pause every 5 minutes of operation, to break the rare earth element segregation. The concentration boundary layer of earth ions on the cathode surface ensures the simultaneous reduction of the five elements and the formation of a homogeneous solid solution. During the last hour of this process, the protective atmosphere is switched to a mixture of 95% argon and 5% hydrogen (by volume), which is introduced into the space above the molten salt at a flow rate of 200 mL / min. The hydrogen participates in chemical reduction, further removing the oxygen content of the powder to an extremely low level. After electrolysis, the cathode block is lifted from the molten salt surface under argon protection and allowed to cool naturally to room temperature. The cathode block is then removed and repeatedly soaked in deionized water with mechanical stirring, changing the deionized water every 2 hours for 12 hours to fully dissolve and remove the adhering chloride molten salt. It is then soaked in 5% dilute acetic acid for 1 hour to neutralize any possible calcium oxides. Finally, it is rinsed three times with anhydrous ethanol and dried in a vacuum drying oven at 60°C for 24 hours. The dried, loose block is then ground and passed through a 300-mesh sieve to obtain pre-alloyed powder, which is then sealed and stored for later use. (4) The pre-alloyed powder is subjected to two-step SPS sintering. The first step is the pre-densification stage: the temperature is increased to 750℃ at a rate of 100℃ / min and held for 5min. During this period, the pressure is increased to 40MPa. In this stage, surface diffusion and local plastic deformation occur between powder particles, achieving preliminary densification while retaining the nanostructure inside the powder. The second step is the full densification stage: the temperature is increased to 900℃ at a rate of 80℃ / min and held for 3min. During this period, the pressure is increased to 50MPa and maintained. In this stage, the bulk is fully densified. Under the combined action of high temperature and electric field, boron reacts with titanium to generate titanium boride whiskers in situ. Yttrium oxide plays the role of grain boundary inhibitor in this stage, pinning grain boundary migration. After sintering, it is rapidly cooled with the furnace to obtain a dense alloy bulk with a diameter of 20mm and a height of 10mm. (5) The SPS sintered block was held at 950℃ for 45 min, and then quickly immersed in an ice-salt mixture for quenching and cooling. The silver phase precipitated during the sintering stage was re-dissolved into the matrix to form a supersaturated solid solution. Then, a two-stage pulse aging treatment was performed: the first-stage aging stage was for the pre-precipitation of silver nano-islands. The quenched block was placed in a vacuum tube furnace and held at 400℃ for 6 h. During this stage, silver atoms were uniformly precipitated from the supersaturated solid solution to form diffusely distributed silver nano-islands with a size of 10 nm. At the same time, boron atoms began to agglomerate, which provided a driving force for the further growth of titanium boride. The second-stage pulse aging stage was for the directional growth and microstructure coupling of titanium boride. Copper electrodes were attached to both ends of the block after the first-stage aging and connected to a pulse power supply. A pulse current was applied under argon protection with a peak current density of 80 A / mm. 2 The pulse width was 2 ms, the frequency was 80 Hz, the on-time to off-time ratio was 1:3, and the total processing time was 30 min. Driven by both thermal and non-thermal effects of the pulsed current, titanium boride underwent directional growth using precipitated silver nanoislands as heterogeneous nucleation sites, ultimately forming a physical film of silver enriched at the tips of titanium boride whiskers and Ag. + A dual-effect antibacterial system combining chemical sterilization and disinfection. Power is cut off after treatment, and the system cools naturally in an argon gas flow. (6) Sodium silicate nonahydrate, potassium hydroxide, lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, silver nitrate, and deionized water were mixed in a mass ratio of 15:3:1:1:0.3:1000 and stirred at 300 rpm for 15 min at room temperature to obtain an electrolyte. The aged block was connected with an aluminum wire as the anode, and a stainless steel electrolytic cell was used as the cathode. The electrolyte was added to perform composite micro-arc oxidation treatment. The first stage was constant current film formation: at a current density of 10 A / dm 2Under the conditions of a pulse frequency of 800Hz and a duty cycle of 20%, the voltage is gradually increased from 0 to 400V to generate a porous titanium dioxide base film. The second stage is constant-voltage densification and elemental doping: the voltage is stabilized at 400V and maintained for 3 minutes, then increased to 450V in a gradient of 5V every 10 seconds, followed by constant-voltage treatment until the current density decays to 1A / dm³. 2 After the treatment was terminated, the material was placed in deionized water and hydrothermally treated at 80°C for 2 hours to seal any remaining micropores in the membrane. Subsequently, it was vacuum dried at 60°C for 12 hours to obtain the antibacterial titanium-silver alloy material. Example 5

[0022] (1) Titanium dioxide, silver oxide, boron oxide, lanthanum oxide, cerium oxide and yttrium oxide with a particle size of 100 nm were mixed in a mass ratio of 9.5:4:0.3:0.3:0.3:0.15. Anhydrous ethanol was used as the medium and the mixture was wet-milled at 300 rpm for 5 h with a ball-to-material ratio of 5:1. The slurry after milling was vacuum-dried at 80 °C for 12 h and then ground through a 200-mesh sieve to obtain a uniformly mixed precursor powder. (2) The mixed precursor powder was cold-pressed at 10 MPa on a uniaxial press to form a cylindrical block with a diameter of 20 mm and a thickness of 5 mm. The block was placed in a tube furnace and heated to 950 °C at 5 °C / min under argon protection, and held for 3 h for pre-sintering. After cooling in the furnace, the block was removed. The pre-sintered block was bound and fixed with molybdenum wire as an electrolytic cathode. Anhydrous calcium chloride, anhydrous calcium fluoride and anhydrous sodium chloride were mixed at a mass ratio of 9.5:6:4. Under a high-purity argon atmosphere, the mixture was heated to 850 °C at 5 °C / min. After the molten salt was completely melted and stabilized, the pre-sintered cathode block was immersed in the molten salt. A high-purity graphite rod with a diameter of 10 mm was used as the anode for multi-element molten salt pulse co-reduction. (3) The first stage lasts for a total of 3 hours. First, the cathode potential is set to -1.8V and the pulse duty cycle is 1:2, that is, energizing for 10 milliseconds and de-energizing for 20 milliseconds. Titanium dioxide is partially reduced to porous titanium hydride. The generated nanopores are used to physically adsorb lanthanum ions, cerium ions and borate ions in the molten salt to achieve atomic-level uniform dispersion and suppress rare earth element segregation from the source. Second, the second stage lasts for a total of 8 hours. First, the cathode potential is set to -2.2V and the pulse duty cycle is 1:1, that is, energizing for 15 milliseconds and de-energizing for 15 milliseconds. At the same time, an ultrasonic field is applied to the molten salt area at 20kHz, with a 2-minute pause every 5 minutes of operation, to break the rare earth element segregation. The concentration boundary layer of earth ions on the cathode surface ensures the simultaneous reduction of the five elements and the formation of a homogeneous solid solution. During the last hour of this process, the protective atmosphere is switched to a mixture of 95% argon and 5% hydrogen (by volume), which is introduced into the space above the molten salt at a flow rate of 200 mL / min. The hydrogen participates in chemical reduction, further removing the oxygen content of the powder to an extremely low level. After electrolysis, the cathode block is lifted from the molten salt surface under argon protection and allowed to cool naturally to room temperature. The cathode block is then removed and repeatedly soaked in deionized water with mechanical stirring, changing the deionized water every 2 hours for 12 hours to fully dissolve and remove the adhering chloride molten salt. It is then soaked in 5% dilute acetic acid for 1 hour to neutralize any possible calcium oxides. Finally, it is rinsed three times with anhydrous ethanol and dried in a vacuum drying oven at 60°C for 24 hours. The dried, loose block is then ground and passed through a 300-mesh sieve to obtain pre-alloyed powder, which is then sealed and stored for later use. (4) The pre-alloyed powder is subjected to two-step SPS sintering. The first step is the pre-densification stage: the temperature is increased to 750℃ at a rate of 100℃ / min and held for 5min. During this period, the pressure is increased to 40MPa. In this stage, surface diffusion and local plastic deformation occur between powder particles, achieving preliminary densification while retaining the nanostructure inside the powder. The second step is the full densification stage: the temperature is increased to 900℃ at a rate of 80℃ / min and held for 3min. During this period, the pressure is increased to 50MPa and maintained. In this stage, the bulk is fully densified. Under the combined action of high temperature and electric field, boron reacts with titanium to generate titanium boride whiskers in situ. Yttrium oxide plays the role of grain boundary inhibitor in this stage, pinning grain boundary migration. After sintering, it is rapidly cooled with the furnace to obtain a dense alloy bulk with a diameter of 20mm and a height of 10mm. (5) The SPS sintered block was held at 950℃ for 45 min, and then quickly immersed in an ice-salt mixture for quenching and cooling. The silver phase precipitated during the sintering stage was re-dissolved into the matrix to form a supersaturated solid solution. Then, a two-stage pulse aging treatment was performed: the first-stage aging stage was for the pre-precipitation of silver nano-islands. The quenched block was placed in a vacuum tube furnace and held at 400℃ for 6 h. During this stage, silver atoms were uniformly precipitated from the supersaturated solid solution to form diffusely distributed silver nano-islands with a size of 10 nm. At the same time, boron atoms began to agglomerate, which provided a driving force for the further growth of titanium boride. The second-stage pulse aging stage was for the directional growth and microstructure coupling of titanium boride. Copper electrodes were attached to both ends of the block after the first-stage aging and connected to a pulse power supply. A pulse current was applied under argon protection with a peak current density of 80 A / mm. 2 The pulse width was 2 ms, the frequency was 80 Hz, the on-time to off-time ratio was 1:3, and the total processing time was 30 min. Driven by both thermal and non-thermal effects of the pulsed current, titanium boride underwent directional growth using precipitated silver nanoislands as heterogeneous nucleation sites, ultimately forming a physical film of silver enriched at the tips of titanium boride whiskers and Ag. + A dual-effect antibacterial system combining chemical sterilization and disinfection. Power is cut off after treatment, and the system cools naturally in an argon gas flow. (6) Sodium silicate nonahydrate, potassium hydroxide, lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, silver nitrate, and deionized water were mixed in a mass ratio of 15:3:1:1:0.3:1000 and stirred at 300 rpm for 15 min at room temperature to obtain an electrolyte. The aged block was connected with an aluminum wire as the anode, and a stainless steel electrolytic cell was used as the cathode. The electrolyte was added to perform composite micro-arc oxidation treatment. The first stage was constant current film formation: at a current density of 10 A / dm 2 Under the conditions of a pulse frequency of 800Hz and a duty cycle of 20%, the voltage is gradually increased from 0 to 400V to generate a porous titanium dioxide base film. The second stage is constant-voltage densification and elemental doping: the voltage is stabilized at 400V and maintained for 3 minutes, then increased to 450V in a gradient of 5V every 10 seconds, followed by constant-voltage treatment until the current density decays to 1A / dm³. 2 After the treatment was terminated, the material was placed in deionized water and hydrothermally treated at 80°C for 2 hours to seal any remaining micropores in the membrane. Subsequently, it was vacuum dried at 60°C for 12 hours to obtain the antibacterial titanium-silver alloy material.

[0023] Comparative Example 1 The difference between the comparative example and Example 3 is that silver oxide was not added during the experiment; the other steps are the same as in Example 3.

[0024] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that boron oxide was not added during the experiment, while the other steps were the same as in Example 3.

[0025] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that lanthanum oxide and cerium oxide are not added, while the other steps are the same as in Example 3.

[0026] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that the gradient potential and pulse mechanism are not used. The entire process uses a constant potential of -2.2V (relative to the graphite anode) and DC mode, and is continuously electrolyzed for 11 hours. The remaining steps are the same as in Example 3.

[0027] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that no aging treatment is performed, while the remaining steps are the same as in Example 3.

[0028] Comparative Example 6 The difference between Comparative Example 6 and Example 3 is that micro-arc oxidation treatment is not performed; the remaining steps are the same as in Example 3.

[0029] Example of effect Table 1 below shows the performance analysis results of the titanium-silver alloy materials of Examples 1 to 5 and Comparative Examples 1 to 6 of the present invention.

[0030]

[0031] Comparison of experimental data on the antibacterial properties of the comparative examples and embodiments revealed that the SPS two-step sintering process in this invention, in conjunction with grain boundary inhibitors, formed TiB whiskers. Furthermore, the dual-stage pulse aging process induced the pre-precipitation of Ag nano-islands and the directional growth of TiB whiskers at the Ag tips, resulting in physical film rupture of the whiskers and the interaction between the whiskers and Ag. + A dual-effect antibacterial system combining chemical sterilization and antimicrobial action significantly enhances the antibacterial performance of the material. Comparison of the compressive strength experimental data from the examples and comparative examples reveals that the salt reduction in this invention utilizes a gradient potential pulse electrolysis mechanism to pre-reduce TiO2 to porous TiH2, leveraging its nanopores to adsorb and disperse La. 3+ Ce 3+ B 3+ Ions are then synchronously pulsed to reduce all oxides, and ultrasound is used to break the rare earth concentration boundary layer to inhibit segregation. Later, an Ar-H2 mixed gas is introduced for deep deoxidation, eliminating the embrittlement of interstitial oxygen atoms and achieving uniform dispersion of all elements, thus endowing the material with excellent mechanical properties. Comparison of the corrosion resistance experimental data from the examples and comparative examples reveals that the micro-arc oxidation in this invention, through rare earth composite electrolyte and gradient voltage film formation, generates a dense film containing La2O3 / CeO2 in situ. This dense film acts as a physical barrier, directly blocking the corrosive medium and greatly improving the corrosion resistance of the material. Simultaneously, it can slowly release La... 3+ / Ce 3+ It disrupts the integrity of bacterial cell membranes, thereby further enhancing antibacterial properties.

[0032] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.

Claims

1. A method for preparing an antibacterial titanium-silver alloy material, characterized in that, Includes the following steps: (1) Titanium dioxide, silver oxide, boron oxide, lanthanum oxide, cerium oxide and yttrium oxide are mixed in a mass ratio of 8.5~9.5:2~4:0.1~0.3:0.1~0.3:0.1~0.3:0.05~0.15, wet-milled for 3~5 hours, vacuum dried at 80℃ for 12 hours and sieved to obtain precursor powder, cold-pressed into blocks, and pre-sintered as electrolytic cathode; anhydrous calcium chloride: anhydrous calcium fluoride: anhydrous sodium chloride are mixed in a mass ratio of 8.5~9.5:4~6:2~4, heated to 850℃ under a high-purity argon atmosphere, the pre-sintered cathode block is immersed in molten salt, and a high-purity graphite rod is used as the anode to perform gradient multi-element molten salt pulse co-reduction to obtain pre-alloy powder; (2) After the pre-alloyed powder is sintered by SPS in two steps, it is kept at 950℃, then quenched and cooled, and then subjected to two-stage pulse aging treatment: the first stage of aging is the pre-precipitation of silver nano islands, and the quenched block is kept at 400℃ for 6 hours. In the second-stage pulse aging process, copper electrodes are added to both ends of the block after the first-stage aging, and connected to a pulse power supply. A pulsed current is applied under argon protection, and the block is then naturally cooled in an argon flow to obtain the final product. (3) The aged block is connected with aluminum wire as the anode and stainless steel electrolytic cell as the cathode. Electrolyte is added and composite micro-arc oxidation treatment is carried out. After the treatment is completed, it is placed in deionized water and hydrothermally treated at 80°C for 2 hours. Then it is vacuum dried at 60°C for 12 hours to obtain antibacterial titanium silver alloy material.

2. The antibacterial titanium-silver alloy material according to claim 1, characterized in that, The titanium dioxide mentioned in step (1) is titanium dioxide with a particle size of 100 nm.

3. The antibacterial titanium-silver alloy material according to claim 1, characterized in that, The sieving in step (1) is: passing through a 200-mesh sieve.

4. The antibacterial titanium-silver alloy material according to claim 1, characterized in that, The cold pressing molding process in step (1) involves cold pressing the mixed precursor powder on a uniaxial press at 10 MPa to form a cylindrical block with a diameter of 20 mm and a thickness of 5 mm.

5. The antibacterial titanium-silver alloy material according to claim 1, characterized in that, The heating rate in step (1) is 5℃ / min.

6. The antibacterial titanium-silver alloy material according to claim 1, characterized in that, The high-purity graphite rod mentioned in step (1) is a high-purity graphite rod with a diameter of 10mm.

7. The antibacterial titanium-silver alloy material according to claim 1, characterized in that, The pre-alloyed powder mentioned in step (1) is: pre-alloyed powder that has passed through a 300-mesh sieve.

8. The antibacterial titanium-silver alloy material according to claim 1, characterized in that, The block after aging treatment in step (2) is a dense alloy block with a diameter of 20 mm and a height of 10 mm.

9. The antibacterial titanium-silver alloy material according to claim 1, characterized in that, The electrolyte in step (3) is prepared by mixing sodium silicate nonahydrate, potassium hydroxide, lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, silver nitrate and deionized water in a mass ratio of 15:3:1:1:0.3:1000 and stirring at room temperature for 15 minutes.

10. The antibacterial titanium-silver alloy material according to claim 1, characterized in that, The composite micro-arc oxidation treatment in step (3) is as follows: The first stage is constant current film formation: at a current density of 10 A / dm 2 Under the conditions of a pulse frequency of 800Hz and a duty cycle of 20%, the voltage is gradually increased from 0 to 400V to generate a porous titanium dioxide base film. The second stage is constant-voltage densification and elemental doping: the voltage is stabilized at 400V and maintained for 3 minutes, then increased to 450V in a gradient of 5V every 10 seconds, followed by constant-voltage treatment until the current density decays to 1A / dm³. 2 termination.